Analisis Kinerja Operasional Pada UMKM Martabak Nicco Narogong Kota Bekasi - Wahyu Suryadinata; Muhamad Lutfi Maulana; Jendro Diu; Dimas Taufiqurahman; Ilham Raka Pratama; Rico Satria; Naura Syahira (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The culinary sector is one of the most popular MSME businesses. With small capital and innovation in food, this business is quite promising considering people's daily needs for food. Martabak is an example of a food that many Indonesians like because it is cheap and easy to get. Martabak UMKM is one of the small and medium businesses that is quite popular in Indonesia. This research aims to analyze the Break Even Point (BEP), Net Present Value (NPV), and Profitability Index (PI) of Martabak MSME businesses to evaluate potential profits and investment risks within a certain period of time. Based on the results of the BEP, NPV and PI analysis, it can be concluded that the Martabak Nicco Narogong Bekasi MSME business has the potential to generate profitable profits. However, a more in-depth evaluation needs to be carried out regarding risk and market factors to make more appropriate investment decisions. It is necessary to develop effective marketing and operational strategies to increase sales and optimize profits in the Martabak MSME business. Apart from that, it is also necessary to consider risk factors that might affect the performance of this business in the future.